Biostory as Indigiqueer Resistance in Indigenous Futurism - Bradley Harvey, Monica (2025)
This essay offers a critical reflection mirroring the book of creative essays Making Love with the Land (2022), by Joshua Whitehead. It defines three concepts within contemporary Indigenous literatures: biostory, Indigiqueer, and Indigenous futurism, braiding a politicized, sovereign writing style within the book. It examines how the concept of biostory functions to help Indigenous, queer and other peoples imagine different ways of being in real/possible apocalyptic present/futures. Queer Indigenous futurisms and Indigiqueer writing disrupts linear conceptualizations of space, time and identity, weaving organic, spiritual, and scientific elements in the construction of self and other.